Integrated management of cogongrass [Imperata cylindrica (L.) Rauesch.] in corn using tillage, glyphosate, row spacing, cultivar and cover cropping - Chikoye, David; Udensi, U.E.; Ogunyemi, S. (Wiley, 2005)
Cogongrass [Imperata cylindrica (L.) Raeusch.] is a major weed in the tropics where land is intensively cultivated and fallow duration is less than 5 yr. Field studies were conducted in 1999 and 2000 in Nigeria to evaluate cogongrass response to combinations of five weed control options. Treatment combinations were tillage (hoe tillage and no-tillage), corn (Zea mays L.), row spacing (50 and 75 cm), corn cultivar [open-pollinated (OP) and hybrid], herbicide (glyphosate and no glyphosate), and cover crop {velvetbean [Mucuna cochinchinensis (Lour) A. Chev] and no velvetbean}. The treatment combinations were arranged in a randomized complete block design with three replications. Integrating tillage, herbicide, and cover cropping with velvetbean gave optimal control of cogongrass. Corn height and leaf area were negatively correlated with cogongrass shoot, rhizome, and total biomass. Corn grain yield was negatively correlated with cogongrass shoot biomass and total cogongrass biomass (shoot + rhizome). Good control of other weeds was achieved through the use of narrow corn row spacing and cover cropping with velvetbean. Tillage, narrow corn row spacing, and the use of herbicide had a positive effect on corn grain yield. The use of competitive cultivars, narrow row spacing, cover crop, and herbicide may be sustainable approaches to the control of cogongrass and other weeds in corn.